Silêncios e espetáculos: leitura comparada de A Cidade Sitiada (1949), de Clarice Lispector e Noites no Circo (1984), de Angela Carter - Oliveira, Kátia Isidoro de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The aim of this thesis is to discuss how the gender issue is represented in literature by pointing out differences and similarities between Clarice Lispector’s A Cidade Sitiada (1949) and Angela Carter’s Nights at the Circus (1984). In A Cidade Sitiada (1949), Lucrécia is a "beleaguered" woman; she is not presented to the reader as the subject of her story, but, rather, an object. She is a foreigner in her world, with what she does not interact, surrounded, exiled by city walls. In her novel Carter shows the process of modernization, love, the perspective of the marginalized, human relations and female freedom. To build the effect of liberation, the author frees herself from closed environments that were part of the settings of her previous novels and opts for an exterior space. And she also chooses as protagonist Fevers, a woman with wings, a powerful image of liberation and female transformation and aware of what she represents. The discoveries of the protagonists are set in the process of social modernization of the late nineteenth and early twentieth century. While in England the woman is born with wings and free, in Brazil she remains trapped in patriarchal society. Lastly, this research paper intends to compare the way in which Clarice Lispector and Angela Carter can discuss the gender issue in literature and break through the lines of patriarchal society. From this point of view, the intention of this thesis is to confront the construction of the female characters in the works and discuss the process of modernization under the eyes of the protagonists in English and Brazilian literatures.

Pretende-se nessa tese discutir como a questão de gênero é representada na literatura apontando as diferenças e proximidades entre a autora brasileira Clarice Lispector e a inglesa Angela Carter em A Cidade Sitiada (1949) e Noites no Circo (1984). Em A Cidade Sitiada (1949), Lucrécia é uma mulher “sitiada”, ela não é apresentada ao leitor como sujeito da sua história, mas, em vez disso, um objeto narrado. É uma estrangeira no mundo onde habita e com o qual não interage, cercada, exilada por muros da cidade. Em seu romance Carter mostra o processo de modernização, o amor, a perspectiva dos marginalizados, as relações humanas e a liberdade feminina. Para colaborar com o efeito de libertação, a autora livra-se de ambientes fechados que faziam parte do cenário de seus romances anteriores e opta pelo espaço exterior. E ainda opta pela protagonista Fevvers, a mulher com asas, que em si carrega uma poderosa imagem de libertação e transformação feminina e tem consciência do que representa. As descobertas das protagonistas estão ambientadas no processo de modernização social de fins do século XIX e início do século XX. Enquanto na Inglaterra a mulher nasce com asas e livre, no Brasil a mulher ainda continua presa no sistema de sociedade patriarcal. Diante do exposto, pretende-se neste trabalho comparar o modo como Clarice Lispector e Angela Carter conseguem discutir a questão de gênero na literatura e transpor as linhas do patriarcado na sociedade. Sob tal prisma a intenção dessa tese é confrontar e aprofundar a construção das personagens femininas nas obras.
Silences and spectacles: a comparative reading of Clarice Lispector’s A Cidade Sitiada (1949) and Angela Carter’s Nights at the Circus (1984)
Keywords: Literatura comparada; Literatura de autoria feminina; Angela Carter; Noites no Circo; Clarice Lispector; A Cidade Sitiada